2008
DOI: 10.1080/02640410701422076
|View full text |Cite
|
Sign up to set email alerts
|

Elite football on artificial turf versus natural grass: Movement patterns, technical standards, and player impressions

Abstract: The aim of the present study was to examine the movement patterns, ball skills, and the impressions of Swedish elite football players during competitive games on artificial turf and natural grass. Time - motion analyses (36 observations) and technical analyses (16 team observations) were performed and 72 male and 21 female players completed a questionnaire. No differences were observed between artificial turf and natural grass in terms of total distance covered (mean 10.19 km, s = 0.19 vs. 10.33 km, s = 0.23),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

18
183
7
15

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 209 publications
(223 citation statements)
references
References 12 publications
18
183
7
15
Order By: Relevance
“…Thus more pronounced differences may be found in future research comparing performances on surfaces with greater differences in terms of hardness. In summary, the findings support previous research where the surface hardness of natural grass has been found to influence soccer player's performance in terms of their technical and turn frequencies and time spent performing locomotive movements (Andersson et al, 2008;Potthast et al, 2010) although further research is needed to investigate the physiological and biomechanical responses when surface hardness changes.…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…Thus more pronounced differences may be found in future research comparing performances on surfaces with greater differences in terms of hardness. In summary, the findings support previous research where the surface hardness of natural grass has been found to influence soccer player's performance in terms of their technical and turn frequencies and time spent performing locomotive movements (Andersson et al, 2008;Potthast et al, 2010) although further research is needed to investigate the physiological and biomechanical responses when surface hardness changes.…”
Section: Discussionsupporting
confidence: 79%
“…The study aimed to compare soccer performances on surfaces of contrasting hardness and provides evidence suggesting natural grass surface hardness has an impact on game activity and locomotive movements in soccer which concurs with previous findings (Andersson et al, 2008;Potthast et al, 2010). The frequency of high intensity shuffling was significantly greater on softer grass when compared to harder grass (p<0.05).…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…Although it's important to remain pragmatic, as match running performance is complex as factors such as context (Castellano, Blanco-Villasenor, & Alvarez, 2011), technical level (Rampinini, Impellizzeri, Castagna, Coutts, & Wisloff, 2009), formation (Bradley et al, 2011), the opponent (Rampinini, Coutts, Castagna, Sassi, & Impellizzeri, 2007), seasonal period (Rampinini et al, 2007), fatigue/pacing (Bradley & Noakes, 2013), surface (Andersson, Ekblom, & Krustrup, 2008) and the environment (Mohr, Nybo, Grantham, & Racinais, 2012), all interact and impact on match running performances. Another factor thought to impact on the physical demands of match play is team BP.…”
Section: Discussionmentioning
confidence: 99%
“…Most research has explored the physical (Di Salvo, Gregson, Atkinson, Tordoff, & Drust, 2009) and technical requirements of match-play in isolation (Collet, 2013) but few studies have integrated these facets of match-play to gain a more holistic understanding of soccer performance (Andersson, Ekblom & Krustrup, 2008). This is especially important given that team success is multifactorial (Van Winckel et al, 2014).…”
Section: Introductionmentioning
confidence: 99%